Aspects of the translation technique of the Septuagint : the finite verb in the Septuagint of Deuteronomy - Nieuwoudt, Bernard Andre (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 1992.